Outline of the relationship between Cardenas’ policies and San Luis de Potosí’s Freemasonry - Sánchez Leija, Luis Manuel (2021)
The following text reviews the possible influence of the ideological project of President Lazaro Cardenas in the practice of Freemasonry in the state of San Luis Potosi, Mexico.  We referred to the documents belonging to the historical archive of the Grand Lodge of Sovereign e Independent “El Potosí” with the intention to continue further research concerning Cardenas’ policies.